Literature Review on Adaptive Optics - Mhnd Farhan (Program Studi Fisika, Fakultas Sains dan Teknologi, Universitas Samudra, 2026)
Adaptive optics (AO) is defined as a technology developed to compensate for wavefront distortions caused by atmospheric turbulence or microscopic heterogeneities, thereby enhancing image quality in observational astronomy and biological microscopy. It utilizes devices such as deformable mirrors or spatial light modulators to detect and correct these distortions for improved imaging. In adaptive optics, a deformable mirror is incorporated into the optical system. This mirror measures wave aberration in real time to correct distortions, reducing environmental impacts and improving imaging quality. Essentially, adaptive optics actively corrects errors in optical systems, combining scientific principles with engineering applications to play a crucial role in modern optics. This paper serves as a review on adaptive optics.